Author Response: Normobaric Hyperoxia Combined With Endovascular Treatment for Patients With Acute Ischemic Stroke: A Randomized Controlled Clinical Trial. (6th December 2022) - Li, Weili; Qi, Zhifeng; Ji, Xunming; Liu, Ke Jian
Abstract : We agree with the opinion expressed by Dr. Pensato. 1 There are 2 practical approaches to save the ischemic penumbra: shortening time to complete recanalization and minimizing penumbra loss through neuroprotection strategies. Our normobaric hyperoxia (NBO) plus endovascular therapy approach focused on the later strategy. Although clinical outcome is the ultimate test of neuroprotection, it is desirable to be able to follow the reversion of the ischemic core in NBO patients through real time imaging techniques, which demonstrate how the better clinical outcome is achieved. Therefore, in the coming era of neuroprotection in the ischemic penumbra, it is urgent to develop and implement new imaging techniques, or refine the CT perfusion thresholds, to accurately reflect the size of the ischemic core.